Facilitators and barriers of reducing sedentary behavior in sedentary and non-sedentary older adults: a descriptive qualitative study based on the COM-B model and TDF - Siqing Chen; Kaijie Yang; Albert Ko; Edward Giovannucci; Matthew Stults-Kolehmainen; Lili Yang (BMC Public Health)
Abstract Background Prolonged sedentary behavior is a critical health risk for older adults. However, little is known about the distinct barriers and facilitators experienced by sedentary and non-sedentary older adults. Understanding these factors is essential for designing effective behavior change interventions. Purpose The study aims to identify and categorize the barriers and facilitators to reducing sedentary behavior among sedentary and non-sedentary older adults using the Capability, Opportunity, Motivation-Behavior (COM-B) model and Theoretical Domains Framework (TDF), thereby informing future mobile health (mHealth) interventions designed to reduce sedentary time in this population. Methods Data were collected through semi-structured interviews with older adults, conducted at two community hospitals in China between July 2024 and September 2024. The interviews focused on older adults’ psychological and physical capabilities, social and physical opportunities, and reflective and autonomous motivations related to sedentary behavior. According to the Canadian 24-Hour Movement Guidelines, participants were classified as sedentary (> 8 h/day sitting time) or non-sedentary (≤ 8 h/day) based on a participant characteristics questionnaire with verbal confirmation during the interview. The data were analyzed thematically, and the identified themes were mapped onto the COM-B model and TDF. Study procedures followed the COREQ checklist for qualitative research reporting. Results The study included 29 older adults, comprising 19 sedentary (65.5%) and 10 non-sedentary (34.5%). The following ten higher-order themes were identified: Lack of Knowledge (and Limited Knowledge); Lack of Methods (and Available Methods); Sedentary Triggers (and Interruptions); Lack of Management (and Self-management); Lack of Social Support (and Available Social Support); Lack of Environmental Support (and Available Environment Support); Perceptions and Conflicts (and Importance and Effort); Lack of Confidence (and Confidence); Limited Belief (and Understanding Health Benefits); and Limited Motivation (and Sufficient Motivation). Conclusion Sedentary older adults face barriers such as low awareness of health risks, lack of regulation strategies, and insufficient social support, while non-sedentary older adults demonstrate higher confidence, better self-regulation, and engage in structured activities supported by cues such as mobile health reminders.